The growth of the Euro-dollar market : an appraisal of its domestic and international implications - Owens, Jeffrey (Cardiff : University of Wales Press, 1974)
This study is aimed at exploring the rapid growth of the EURO-Dollar market
Bibliography: p. 165-167.
ijb, 18/01/2019
Loans
Keywords: Euro-dollar market